In utero exposure to Onchocerca volvulus: relationship to subsequent infection intensity and cellular immune responsiveness. - Elson, L H (1996)
Afro-Ecuadorian individuals from an area where Onchocerca volvulus is hyperendemic have been monitored for infection over the past 16 years. To determine whether in utero exposure to O. volvulus biases a child's subsequent immune responses, children (9 to 16 years old) for whom the mother's infection status was known were chosen for study. Children of infected mothers (n = 19) had significantly higher levels of skin microfilariae than children of uninfected mothers (n = 13; P = 0.021). While the serum levels of O. volvulus-specific immunoglobulin G (IgG), IgG subclasses, and IgE showed no significant differences between the two groups of children, peripheral blood mononuclear cells of children of infected mothers produced higher levels of Th2-type cytokines to several parasite antigens and lower levels of Th1-type cytokines to nonparasite antigens than those of children of uninfected mothers. Thus, in utero exposure to O. volvulus has a long-term effect on the child's subsequent cellular immune response that may render the child more susceptible to O. volvulus infection postnatally.